A parametric study of cohesive particle agglomeration in a shear flow—numerical simulations by the discrete element method. Issue 5 (4th May 2017) - Hellestø, Aslak S.; Ghaffari, Maryam; Balakin, Boris V.; Hoffmann, Alex C.
ABSTRACT: In this study, we investigate numerically the shear-induced agglomeration of cohesive inertial particles in a simple shear flow. We conduct a series of numerical simulations by implementing a soft-sphere collision model. Post-processing tools are developed in-house to analyze the results of the simulations in terms of transient and terminal numbers of primary particles and agglomerates, magnitudes and distributions of agglomerate size, and fractal dimension as functions of the salient physical parameters. The obtained numerical results compared with existing transient models suggest that, as the system transitions from formation of duplets to larger agglomerates, in most cases the number of agglomerates in the system reveals clear maxima. The results also show evidence of agglomerate densification, as weaker agglomerates with lower fractal dimensions are broken up and stronger ones with higher fractal dimensions are formed. Furthermore, we found that a simple theoretical model proposed by, among others, Chimmili et al. is able to predict the temporal development of the agglomerate size properly. GRAPHICAL ABSTRACT: